An Architecture to Develop Multimodal Educative Applications with Chatbots. (22nd March 2013) - Griol, David; Callejas, Zoraida
Animated characters are beginning to be used as pedagogical tools, as they have the power to capture students' attention and foster their motivation for discovery and learning. However, in order for them to be widely employed and accepted as a learning resource, they must be easy to use and friendly. In this paper we present an architecture that facilitates building interactive pedagogical chatbots that can interact with students in natural language. Our proposal provides a modular and scalable framework to develop such systems efficiently. Additionally, we present Geranium, a system that helps children to appreciate and protect their environment with an interactive chatbot developed following our scheme.